2021
DOI: 10.5194/tc-15-1889-2021
|View full text |Cite
|
Sign up to set email alerts
|

On the attribution of industrial-era glacier mass loss to anthropogenic climate change

Abstract: Abstract. Around the world, small ice caps and glaciers have been losing mass and retreating since the start of the industrial era. Estimates are that this has contributed approximately 30 % of the observed sea-level rise over the same period. It is important to understand the relative importance of natural and anthropogenic components of this mass loss. One recent study concluded that the best estimate of the magnitude of the anthropogenic mass loss over the industrial era was only 25 % of the total, implying… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
2
3

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 42 publications
0
29
2
3
Order By: Relevance
“…Attribution studies within glaciology have thus far focused on mountain glacier losses over the industrial era (Marzeion et al, 2014;Roe et al, 2017Roe et al, , 2021. These studies require models that accurately capture how glacier dynamics integrate both long-term trends and short-term climate variability, and have shown that the loss of mountain glaciers over the industrial era is clearly attributable to anthropogenic forcing, both for the metrics of terminus retreat (Roe et al, 2017) and mass balance (Roe et al, 2021). Indeed, the kilometer-scale retreats of mountain glaciers are some of the most statistically robust indicators of anthropogenic climate change observed in the Earth system (Roe et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Attribution studies within glaciology have thus far focused on mountain glacier losses over the industrial era (Marzeion et al, 2014;Roe et al, 2017Roe et al, , 2021. These studies require models that accurately capture how glacier dynamics integrate both long-term trends and short-term climate variability, and have shown that the loss of mountain glaciers over the industrial era is clearly attributable to anthropogenic forcing, both for the metrics of terminus retreat (Roe et al, 2017) and mass balance (Roe et al, 2021). Indeed, the kilometer-scale retreats of mountain glaciers are some of the most statistically robust indicators of anthropogenic climate change observed in the Earth system (Roe et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Often, a single metric is chosen to be minimized (e.g., the model's RMSE with respect to observed in situ mass balances). Rye et al (2012) suggested multi-objective optimization for a (regional) glacier model, striving for Pareto optimality (Marler and Arora, 2004), to constrain parameters more robustly.…”
Section: Introductionmentioning
confidence: 99%
“…Over the long-term, wetlands will likely shrink in size and lead to soil desiccation and wetland degradation (Jacobsen & Dangles, 2017;Polk et al, 2017). In addition, the lagged response time of glaciers to global climate change might exacerbate the climatic debt already experienced by high-alpine communities (Roe et al, 2021;Zekollari et al, 2020). Within two to three decades short-term effects of glacier melt include the displacement and shrinkage of…”
Section: High Elevation (Alpine) Ecosystems and Biodiversitymentioning
confidence: 99%